Sport - A cultural history - Mandell, R. (1984)
Today's calender is set in the minds of many people by the World Series, Wimbledon, the Super Bowl, and the World Cup, rather than by months and days. Sport must mean something. What? Richard Mandell's Sport: A Cultural History shows that sport has always vividly illustrated and reinforced the existing social and moral order. Considering that much of modern sport has evolved in England and America, it is remarkable that so few comprehensive serious studies of sport have appeared in English. This fascinatingly written, generously illustrated volume fills a gap in the literature of world cultural history. The author deals here not only with sport in the classical world where the Olympics were born, but also with sport in early industrial England, China, Japan, and modern America.